THE ROLE OF CONTEXTUAL LEARNING IN EMBEDDING RELIGIOUS MODERATION VALUES IN PAI SUBJECTS - Aisih, Lum Atul; Saihan, Saihan; Indrianto, Nino (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
Contextual learning is an approach that links teaching materials with the real life of students, so that learning is more meaningful. so that learning is more meaningful. This article aims to analyze the role of contextual learning in instilling values of religious moderation in Islamic Religious Education (PAI) subjects. moderation in Islamic Religious Education (PAI) subjects. Moderation religious moderation becomes an urgent need in a multicultural society to prevent extremism and radicalism. prevent extremism and radicalism. This research method uses descriptive qualitative approach with data collection techniques through observation, interviews, and documentation studies. The results showed that contextual approach in PAI subjects is effective in building a moderate understanding of religion through the understanding of religion through student-centered learning strategies. learning strategy that is student-centered. This learning encourages students to think critical, reflective, and tolerant in facing differences. This research recommends the application of contextual learning as an effective method to instill religious moderation values in the educational environment.